Studi Survei Penggunaan Waktu Jam Kosong pada Siswa Kelas XI di SMK Banten Jaya - Huswatun Hasanah; Mentari Andhayani; Firdaus Firdaus (Departement of Mathematics Education, 2023)
Education is one of the many factors that contribute to the country's progress and is the main key to improving the nation's quality. One effort to improve the quality of education is to enhance the quality of human resources, namely teachers. In fact, teachers often cannot teach because have assignments that prevent them from teaching. This causes empty hours in the class so that students get less attention and supervision from the teacher. As a result, student delinquency often occurs at school. This study aims to determine the activities carried out by class XI students of Banten Jaya Vocational School during empty hours. This study uses a survey method that describes the condition of the research sample, namely what activities are carried out by class XI students of Banten Jaya Vocational School during free hours in class. Retrieval of data using a questionnaire. The subjects of this study were 22 students of class XI at Banten Jaya Vocational School. The results showed that the activity most frequently carried out by students was sleeping, reaching 41%.